Pharmacological Characteristics of Porcine Orexin 2 Receptor and Mutants - Liu, Min; Min, Tianqi; Zhang, Haijie; Liu, Yuan; Wang, Zhiqiang (Frontiers in Endocrinology, 2020)
Orexin receptors (OXRs) play a critical regulatory role in central control of food intake, maintenance of sleeping states, energy metabolism, and neuroendocrine homeostasis. However, most previous studies have focused on the sleep-promoting functions of OXRs in human beings, while their potential value in enhancing food intake for livestock breeding has not been fully exploited. In this study, we successfully cloned porcine orexin 2 receptor (pOX2R) complementary DNA and constructed four pOX2R mutants (P10S, P11T, V308I, and T401I) by site-directed mutagenesis, and their functional expressions were further confirmed through Western blotting analysis. Pharmacological characteristics of pOX2R and their mutants were further investigated. These results showed that the P10S, P11T, and T401I mutants had decreased cAMP signaling with orexin A, whereas only the P11T mutant decreased under the stimulation of orexin B. Besides, only P10S displayed a decreased calcium release in response to both orexin ligands. Importantly, these mutants exhibited decreased phosphorylation levels of ERK1/2, p38, and CREB to some degree compared with wild-type pOX2R. Collectively, these findings highlight the critical role of these mutations in pOX2R signaling and expand our understanding of molecular and pharmacological characterization of pOX2R.